When a man loves a woman - Touchstone Home Video (Firm). (Burbank, Calif. Touchstone Home Video, 1999)
Alice and Michael are a passionate couple whose once-stable marriage is rocked by her increasing dependence on alcohol. As they strive to overcome this challenge, they discover a renewed sense of love and commitment.
Library has: VDR-1654 (2 VCDs)
Originally released as a motion picture in 1994.
Special features include: Theatrical trailer.
Director of photography, Lajos Koltai ; editor, Garth Craven ; music by Zbigniew Preisner ; costume design, Linda Bass.
Andy Garcia, Meg Ryan, Lauren Tom, Ellen Burstyn, Philip Seymour Hoffman, Tina Majorino, Mae Whitman.
VCD.
Keywords: Women alcoholics -- Family relationships -- Drama; Alcoholics' spouses -- Drama; Man-woman relationships -- Drama; Fathers and daughters -- Drama; Love -- Drama; Feature films; Romance films; Films for the hearing impaired